Upaya Peningkatan Kemampuan Mengenal Huruf Hijaiyah Pada Anak Usia Dini Dengan Berbantuan Buku Iqro’ - Dini Nurbayinah; Putri Asilestari; Citra Ayu (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research is motivated by the lack of children's ability to recognize hijaiyah letters, differentiate hijaiyah letters and have not been able to pronounce hijaiyah letters correctly. This study aims to explain efforts to improve the ability to recognize hijaiyah letters in early childhood with the help of the iqro' book at TK IT Khadijah Al Kubro. This type of research is classroom action research (PTK). This study consists of two cycles, consisting of four stages, namely: planning, action, observation, and reflection. The subjects of this study were group B, totaling 15 people. The results of the research and assessment of this PTK showed that there was an increase in the ability to recognize hijaiyah letters in early childhood with the help of the iqro' book, namely: it was proven that in the pre-cycle it was only 20%, increasing in cycle 1 to 33.3%, until in cycle 2 it reached a maximum increase of 87%. In addition, the efforts made by teachers in introducing the hijaiyah letters to early childhood at TK IT Khadijah Al Kubro are one by one reciting or reading the hijaiyah letters guided by the teacher using the iqro book. In addition, teachers also introduce the hijaiyah letters by writing several hijaiyah letters on the board.